A 6-year safety surveillance of 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) in South Korea - Soon Min Lee; Jang Hoon Lee; Eun Song Song; Sung Jin Kim; Joon Hyung Kim; Rupert W. Jakes; Raghavendra Devadiga; Moon Sung Park (Human Vaccines & Immunotherapeutics, 2018)
In 2010, Korea introduced 10-valent pneumococcal conjugate vaccine for children aged 6 weeks to 5 years against invasive disease caused by Streptococcus pneumoniae serotypes 1, 4, 5, 6B, 7F, 9V, 14, 18C, 19F, 23F and cross-reactive 19A. The aim of this 6-year real-world study of 646 healthy Korean children from 16 centers vaccinated in routine practice is to monitor vaccine safety, as per Ministry of Food and Drug Safety regulations. Around 50% had a past or existing medical condition, 19.3% an existing condition and 7.6% received concomitant medication). Total of 489 recorded adverse events (AEs) were reported in 274 infants; 86% were mild and the rest moderate, only three were reported as serious. Most AEs (97.8%) were not related to vaccination; one case of injection-site swelling and of fever was related, two cases of fever were probably related, five cases of fever and one case each of diarrhea and coughing were possibly related. None of the serious AEs were related to vaccination. Of 11 adverse drug reactions (ADRs) in 10 subjects, none were serious. Overall, 263 subjects (40.7%) received medication (mainly antibiotics or antipyretics) for the treatment of an AE, of which 6 subjects were treated for an ADR. There was no difference in the incidence of AEs according to age, sex or concomitant vaccination. Subjects with an existing medical condition had significantly more AEs than those without any conditions (p = 0.03), but no differences regarding ADRs. Four-dose vaccination with PHiD-CV appears to have a clinically-acceptable safety profile for Korean children. ClinicalTrials.gov identifier: NCT01248988